2016
DOI: 10.1021/acsami.6b04526
|View full text |Cite
|
Sign up to set email alerts
|

Direct Growth of Graphene Films on 3D Grating Structural Quartz Substrates for High-Performance Pressure-Sensitive Sensors

Abstract: Conformal graphene films have directly been synthesized on the surface of grating microstructured quartz substrates by a simple chemical vapor deposition process. The wonderful conformality and relatively high quality of the as-prepared graphene on the three-dimensional substrate have been verified by scanning electron microscopy and Raman spectra. This conformal graphene film possesses excellent electrical and optical properties with a sheet resistance of <2000 Ω·sq(-1) and a transmittance of >80% (at 550 nm)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…[1][2][3][4] As an important component of wearable devices, pressure sensors, with the ability to emulate the sensory properties of skin by converting pressure stimulation into detectable electrical signals, are critical for applications in healthcare monitoring, [5][6][7][8][9][10] soft robotics, [11][12][13] and prosthetics. [14][15][16] In terms of the sensing mechanism,s everalt ypes of pressure sensors, including piezoresistive, [17][18][19][20][21] piezoelectric, [22][23][24] and capacitive sensors have been reported. Among them, capacitive pressure sensors utilizing ap ressure-induced capacitance change have received significant attention for their low energy consumption, fast response time, low detection limit, and sensing stability.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] As an important component of wearable devices, pressure sensors, with the ability to emulate the sensory properties of skin by converting pressure stimulation into detectable electrical signals, are critical for applications in healthcare monitoring, [5][6][7][8][9][10] soft robotics, [11][12][13] and prosthetics. [14][15][16] In terms of the sensing mechanism,s everalt ypes of pressure sensors, including piezoresistive, [17][18][19][20][21] piezoelectric, [22][23][24] and capacitive sensors have been reported. Among them, capacitive pressure sensors utilizing ap ressure-induced capacitance change have received significant attention for their low energy consumption, fast response time, low detection limit, and sensing stability.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, piezoresistive sensing materials are mostly concentrated in the elastomer composites with incorporated conductive fillers such as conductive polymers (CPs), metal particles, carbon nanotubes (CNTs), and reduced graphene oxide (rGO) into elastomers (e.g., polyurethane (PU) and polydimethylsiloxane (PDMS)) . Most recently, some conductive fibers with unique properties like biocompatibility, and superhydrophobic, and thin films are also served as sensing materials for piezoresistive sensors . For example, Haniff et al reported a plasma‐doping graphene sheet‐based flexible pressure sensor with typical piezoresistive effects .…”
Section: Wearable Sensor Applicationsmentioning
confidence: 99%
“…Generally, pressure sensors transfer the applied pressure into electrical signals based on the piezoelectric, [ 36–40 ] piezoresistive, [ 17,41–45 ] capacitive, [ 46–51 ] or triboelectric sensing mechanism. [ 52–54 ] Figure shows the schematic diagrams of different working mechanisms of pressure sensors.…”
Section: Introductionmentioning
confidence: 99%